Francisco Braga e Sua Música para o Violoncelo - Ferrari, Ângela Maria (2018)
This work presents the cello music written by the Brazilian composer Francisco Braga. In each piece, it was observed aspects such as, the time it was written, different versions, formal structure and tonal harmony. The music already published and the manuscripts were used to gain some knowledge about the composer’s life. Who was Francisco Braga, what we in fact know about him and the reasons to know him better were questions constantly addressed throughout this work. This study took into consideration aspects like the dedication written by the composer, publishers and editors, as well as the words written on the music. Musical and technical aspects were addressed in order to relate Francisco Braga’s cello compositions with the technical issues inherent to the cello. Thus, it was possible with Braga’s opus for the cello to investigate topics like, fingerings, bow strokes, position changes, vibrato, timbre, tempos, dynamics and phrasing. The Etudes used for teaching the cello and Braga’s pieces were related to discuss and exemplify musical and technical issues. Finally, the music for the cello by Francisco Braga provided a reflection about the practice carried out by the researcher as Professor of the Music Department and responsible for the Bachelor's degree in Cello Performance at the Universidade Federal de Santa Maria – UFSM.